Measurement of isotherms and kinetics by volumetric method - Zulqarnain Abdul Halil (2015)
The world is currently facing global warming, with the major cause being the emission of carbon dioxide (CO2) from flue gas released by industrial and power production plants. Technologies have been developed throughout the years, one of them being adsorption technology. Adsorption can be used within power production and industrial plants to reduce CO2 emission, with current ongoing researches being made to improve on this technology. Another usage of this technology can be used in the development of adsorption chillers, which potentially will reduce power consumption in refrigeration processes, leading to power savings through increased efficiency, and ultimately reduce CO2 emission to supply power to these units. In this study, the adsorption capabilities between CO2 adsorption with activated carbon and metal organic frameworks (MOF) and between water vapour adsorption with silica gel is being presented. The activated carbon is of charcoal and MOFs are of MIL-101 and MIL-101S. The adsorption of water vapour on silica gel, CO2 on activated charcoal and on MOFs were done on separate setups each, with more emphasis being made on the setup of water vapour adsorption to study its performance alongside adsorption capabilities of silica gel. The Henry’s isotherm equation was found to fit the experimental data on the uptake of water vapour adsorption with silica gel. However, the current results showed lower uptake values when compared to those of past journals and results from a previous student. It was suspected that the silica gel undergo degradation in its properties. The 1st and 2nd order kinetics equations were also fitted with the kinetics results of water vapour adsorption, with the 2nd order kinetics equations providing better fitting. However, the current data shows better results than that of the previous student’s, with higher uptake and adsorption rate. The reasons of such phenomena are currently inconclusive, with more experiments needed to be made to determine the silica gel properties. Concurrently, the constant volume variable pressure setup (CVVP) were also found to have difficulties in temperature and pressure controls, and leakage issues, with recommendations being made at the end of the report. The Chakraborty-Sun (CS) equation provides good fitting with the total adsorption uptake of CO2 and MIL-101 and MIL-101S, showing a Type I adsorption isotherm. However, current results showed better adsorption uptake within the unaltered MIL-101, whereas a past journal by Anbia with MIL-101 being implemented with MWCNT provides higher adsorption capacity. Hence, additional testing were needed to be made on these adsorbents to determine their properties. On the other hand, the Toth isotherm equation provides good fitting with the excess adsorption uptake of CO2 with activated charcoal, showing a Type I adsorption isotherm. However, the current results also showed lower uptakes than a past journal by Himeno with 5 different types of activated carbons being experimented on. Also, more information regarding the properties of the tested activated charcoal were needed to make conclusive reasonings.